Exploring Amartya Sen's Capability Approach: Insights from Climate Change Adaptation in Indonesia - Ahmad Wasito (Pustaka Peradaban, 2023)
The article delves into the Capability Approach, exploring its concepts and applications, illustrated through its adaptation to climate change challenges in Indonesia. The objective is to enhance understanding and illustrate its effectiveness in addressing climate change impacts. Proposed by Amartya Sen, the Capability Approach provides a holistic view of societal well-being by empowering individuals or groups to achieve life goals. It encompasses various abilities for decent living, including education, health, and freedom. Emphasizing capability enhancement, it transcends economic measures to consider essential aspects shaping human life. Insights into climate change adaptation reveal the Capability Approach's ability to identify the most vulnerable social groups. The article suggests solutions: enhancing capabilities in vulnerable groups and promoting sustainable economic development. By understanding and improving capabilities, along with fostering sustainable economic development, the Capability Approach offers a pathway to address climate change impacts and achieve long-term resilience.